Inovasi Pemberdayaan Ekonomi Pada UKM Jamu Rumah Herbal Mak Nyak di Kabupaten Jember - Fefi Nurdiana Widjayanti; Trias Setyowati (Journal of Community Development, 2021)
The current pandemic condition raises the need to always maintain health and body immunity to be of utmost priority. Herbal medicine as a form of traditional medicine plays an important role in the treatment of population in developing countries, especially Indonesia. The majority of traditional herbal medicine businesses are carried out by home-based business groups, such as traditional herbal medicine businesses carried out by groups of women in Dasa Wisma Aster Dahlia who are domiciled at Tegalbesar Village, Kaliwates District, Jember Regency, produced among others: Jamu Temulawak, Jamu Kunci Sirih, Jamu Kunyit Asem and Jamu Beras Kencur, the herbal medicine which is produced is made from “empon empon” as the base ingredient which is quite abundant in Jember Regency. Herbal medicine business has a very good potential to be developed, because the market demand is very high so that if it is pursued more seriously, it can be used to support the economy of Dama's members. Team acts as: (1) Presenters of socialization, initiator and signing of the MOU document between the two parties, (2) Trainer or assistant for production, monitoring and evaluation (monev) ) post production, packaging and labeling of the final product. Delivering material in the form of lectures, discussions and questions and answers, practice and supervision, continuous monitoring and evaluation to achieve self-sufficiency in production with good product quality. Dama’s members as a socialization participant, also acts as a training participant and mentors the production, marketing, packaging and labeling of the final product.